Acute vesicular eruption postoperatively after use of a forced-air warming device. Issue 3 (4th May 2021) - Austin, Brett; Walterscheid, Brooke; Tarbox, Michelle
Abstract: Thermal burn injuries are a known complication of forced-air warming devices but rarely occur when the device is used in accordance with the manufacturer's instructions. Here we present a case of a 3-year-old girl who in the immediate postoperative period was found to have prominent linear, evenly spaced vesicles and bullae in a pattern that distinctly matched the air-exit perforations of the Bair Hugger device. Clinicians should be aware of potential complications arising from even proper use of a medical device and take all necessary precautions to prevent such incidents.